2017
DOI: 10.1111/acer.13420
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Latino Acculturation and Alcohol Use: Myth Versus Reality

Abstract: Research on health among Latinos often focuses on acculturation processes and the associated stressors that influence drinking behavior. Given the common use of acculturation measures and the state of the knowledge on alcohol-related health among Latino populations, the current analyses tested the efficacy of acculturation measures to predict various indicators of alcohol consumption. Specifically, this quantitative review assessed the predictive utility of acculturation on alcohol consumption behaviors (frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…First, results extended knowledge gained from previous narrative reviews and provided summary effect size estimates for various alcohol use outcomes (Zamboanga et al., ; Zemore, ). By including drinking‐related problems and differentiating alcohol use outcomes, our study also expanded upon findings from another meta‐analysis that examined the associations between acculturation and alcohol consumption among Hispanic adults (Alvarez et al., ). Second, our use of a theoretically and empirically supported conceptualization of acculturation afforded the opportunity to examine how measurement of this construct affected its observed correlations with alcohol use.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…First, results extended knowledge gained from previous narrative reviews and provided summary effect size estimates for various alcohol use outcomes (Zamboanga et al., ; Zemore, ). By including drinking‐related problems and differentiating alcohol use outcomes, our study also expanded upon findings from another meta‐analysis that examined the associations between acculturation and alcohol consumption among Hispanic adults (Alvarez et al., ). Second, our use of a theoretically and empirically supported conceptualization of acculturation afforded the opportunity to examine how measurement of this construct affected its observed correlations with alcohol use.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to research with Asian Americans (Lui and Zamboanga, ), research with Hispanics has shown inconsistent results pertaining to the associations between acculturation and alcohol use outcomes: Whereas some studies showed statistically significant bivariate or multivariate associations, others indicated that acculturation was unrelated to alcohol use (Zamboanga et al., ; Zemore, ). A recent meta‐analysis of 31 studies with Hispanic adults (Alvarez et al., ) showed a modest correlation ( r = 0.16) between acculturation and alcohol consumption (including drinking frequency, average volume, and overall quantity). It remained unknown how acculturation was distinctly linked to various types of alcohol use outcomes, particularly binge drinking and alcohol‐related problems.…”
Section: Alcohol Use and Acculturation Among Hispanic Americansmentioning
confidence: 99%
See 2 more Smart Citations
“…Acculturation refers to the extent to which an individual retains their cultural heritage and/or adopts the receiving society's culture (Berry, 1997). Although studies have found acculturation to be associated with alcohol use among Hispanic youth, recent meta-analyses have indicated that the relationship between acculturation on alcohol use is small (Alvarez, Frietze, Ramos, Field, & Zárate, 2017;Lui & Zamboanga, 2018). 1 Addressing these small effect sizes, Lui and Zamboanga (2018) hypothesized that the sociocultural stress associated with the acculturation process, in addition to acculturation per se, represents a risk for underage alcohol initiation.…”
mentioning
confidence: 99%